The wild pear tree [videorecording (DVD)] - Ceylan, Nuri Bilge, 1959-; Ceylan, Nuri Bilge, 1959-; Demirkol, Doğu, 1985-; Cemcir, Murat, 1976-; Yıldırımlar, Bennu (Cinema Guild, 2019)
Having returned to his family's rural home after university studies in the city, an aspiring writer finds his dreams and aspirations at odds with the ways of his family and other people in the village.